2005
DOI: 10.1016/s1808-8694(15)31326-4
|View full text |Cite
|
Sign up to set email alerts
|

Balance in the elderly

Abstract: It was concluded that the vestibular disorders, according to the vecto-electronystagmography, and to the complaints of dizziness, tinnitus and hearing impairment, are numerically similar in both studied groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 2 publications
0
11
0
5
Order By: Relevance
“…The larger number of complaints in the older group may be associated to the hypothesis that a natural deterioration process occurs in this system over time 21 . One study 19 showed that the number of complaints of dizziness increases with age, as follows: 14% in the 18-39 year age group, 28% in the 40-59 year group and 37% in those 60 years of age or older.…”
Section: Regulatory Guideline No 35 (Nr 35) Work Atmentioning
confidence: 99%
“…The larger number of complaints in the older group may be associated to the hypothesis that a natural deterioration process occurs in this system over time 21 . One study 19 showed that the number of complaints of dizziness increases with age, as follows: 14% in the 18-39 year age group, 28% in the 40-59 year group and 37% in those 60 years of age or older.…”
Section: Regulatory Guideline No 35 (Nr 35) Work Atmentioning
confidence: 99%
“…As cause of this degenerative process, it occurs vertigo and/or dizziness and imbalances in the elderly population [3].…”
Section: Aging Processmentioning
confidence: 99%
“…The imbalance disorders bring big impacts to the daily elderly life, it leads to a reduction of social autonomy which has as consequences: The reduction of daily activities, unsafe feelings and predisposed to falls, it induces to suffering and body immobility [3,7,8].…”
Section: Aging Processmentioning
confidence: 99%
“…To perform these tests, most services suspended the intake of foods high in cafeine, nonessential drugs, tobacco, and alcohol. As for the number of hours of restrictive diet, some authors suggest 72 hours suspension before the exam [27,34,35], some 48 hours before [36], and some even 24 hours before the test [28,37].…”
Section: Cafeine and Vestibular Systemmentioning
confidence: 99%